Designing healthy workspaces: results from Australian certified open-plan offices. Issue 5 (17th September 2020) - Candido, Christhina; Marzban, Samin; Haddad, Shamila; Mackey, Martin; Loder, Angela
Abstract : Purpose: From poor indoor environmental quality conditions to musculoskeletal discomfort, the interior design of workspaces has the potential to negatively affect human health. One of the key responses from industry has been the rise of health-related guidelines, certification and rating tools. Despite the rapid adoption of such tools by the Australian high-end corporate real estate, there is a scarcity of empirical evidence arising from such premises. This study aims to compare results from certified premises against other open-plan offices to understand differences arising from occupants' satisfaction, perceived productivity and health. Design/methodology/approach: A total of 1, 121 post-occupancy evaluation (POE) surveys conducted in 9 offices were analyzed. All these premises hold a certification from the Green Building Council of Australia and two achieved a WELL rating. The analysis is performed in three parts: comparing WELL-certified (2 cases) and non-WELL certified (7 cases) offices along with comparison with a benchmark of 9, 794 POE surveys from the BOSSA database, comparing activity-based working (ABW) (5 cases) and traditional (4 cases) offices along with comparison with BOSSA database and qualitative study of the similar design features in all 9 offices accompanied with an in-depth analysis of the health-related issues that might have occurred because of poor ergonomic design. For the first two parts, several t -tests are performed. Findings: Highest scores for overall satisfaction, workability, perceived productivity and health were reported on WELL-rated premises. Offices incorporating active design principles outperformed others on workability, satisfaction with work area, collaboration, unwanted interruptions, perceived productivity and health. ABW environments outperformed the traditional offices on spatial comfort, thermal comfort, noise and privacy, personal control, comfort of furnishing, adjustability of the work area and space to collaborate. People using sit–stand workstations reported spending significantly less time seated and female workers were more prone to reporting pain over the past 12 months. The best-performing offices implemented active and biophilic design, prioritized overall ergonomics and different spaces designed to support a variety of work-related activities. Originality/value: This research conducts a comparison between certified premises against other offices in terms of occupants' satisfaction, perceived productivity and health. A qualitative analysis is also conducted to investigate personal and physical environmental aspects. The way of working (ABW or traditional), implementation of active design features, self-reported musculoskeletal discomfort and physical activity were also investigated. The study has taken a holistic approach to investigate many health-related physical, environmental and emotional aspects in certified workspaces.